Pengaruh Perbandingan Air Pengekstrak, Suhu Presipitasi, dan Konsentrasi Kalium Klorida (KCL) Terhadap Mutu Karaginan - Arif Rahman Hakim; Singgih Wibowo; Fifi Arfini; Rosmawaty Peranginangin (Jurnal Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
ABSTRACTStudy on carrageenan extraction using filter press with variation ratio of seaweed and extraction medium (water), temperature of precipitation, potassium chloride concentration has beenconducted. Ratio of seaweed and water used were 1:20, 1:30 and 1:40 (w/v), temperature of precipitation were varied at 15 and 30°C, and potassium chloride concentration used were 1 and 1.5%. Parameters observed on the carrageenan were yield, viscosity, gel strength, moisture content, ash content, sulfate content and acid insoluble ash. Result showed that the best treatment was ratio seaweed : water = 1:20, temperature of precipitation at 30°C and potassium chlorideconcentration of 1%, with quality of carrageenan i.e. gel strength 1897.14 (g/cm2), viscosity 145 (cPs), ash content 29.59%, acid insoluble ash 0.83%, sulfate content 18.36%, yield 31.77% andmoisture content 9.73%. The carrageenan quality has met with the standard established by Food Agriculture Organization (FAO), Food Chemical Codex (FCC) and European Economic Community(EEC).